Urgensi Maharah Kitabah (Keterampilan Menulis) dalam Pembelajaran Kaligrafi Al-Qur’an - Hafizatul Hasanah; Lely Triastuti (Jurnal Sathar, 2024)
There are several types of techniques to improve the understanding of al-Kitabah, one of which is khat (calligraphy). Khat is the process of writing neatly, beautifully, so that in learning khat students not only write letters and form words and sentences, but also touch on aesthetic or beautiful aspects, so that it makes them comfortable and at home to continue writing. Therefore, the aim of learning khat is so that students are skilled at writing Arabic letters and sentences correctly and beautifully. The aim of this research is the importance of maximizing calligraphy in improving maharatul kitabah (writing ability) in Arabic. The results of this research are improving the ability to write (maharatul kitabah) in Arabic script, as well as improving the way of writing Arabic letters by studying calligraphy. As is known, calligraphy is the art of beautiful writing. By studying calligraphy, you can easily improve your Arabic writing to be better and in accordance with the rules of Arabic writing.